A magyar mezőgazdasági szakoktatás története 1945-ig, különös tekintettel a debreceni agrár-felsőoktatásra - Surányi, Béla (Gerundium, 2018)
The History of Hungarian Agricultural Vocational Education until 1945, with a special Emphasis on the Agricultural Higher Education of Debrecen. The study mainly provides an overview on the organizational history of educational institutions of the Hungarian agricultural vocational education. It gives a perspective on the development of different types of schools from the lowest level of education, through secondary education to the institutions of the highest level, outlining the economic and social-historical aspects, also with respect to the relevant legislation. A special attention is paid by the author to the history of the agricultural higher education of Debrecen until 1945.